Do consumers always believe humans create better boxes than AI? The context-dependent role of recommender creativity - Im, Hyunjoo; Lee, Garim (International journal of retail & distribution management, 2023)
PurposeThe recent surge of subscription box services calls for research to understand how consumers respond to curation services. This study aims to develop and test a theoretical model to predict consumer response to AI (vs human). Particularly, the authors tested the role of stereotyping in shaping consumer perception of creativity in this context while considering the contextual moderators, shopping goals (hedonic vs utilitarian) and product category (fashion vs meal).Design/methodology/approachTwo preliminary studies and the main study (total n = 761) tested the assumptions and hypotheses of the study. Preliminary study 1 (n = 511 Amazon mTurk, online survey) confirmed consumer stereotypes of humans and machines. Preliminary study 2, a single-factor between-subjects online experiment (recommender: human vs AI), was conducted at a large Midwestern university in the US (n = 56). The main study was conducted as a 2(recommender: human vs AI) × 2(product: fashion vs meal) × 2(goal: utilitarian vs hedonic) between-subjects online experiment (n = 194, Amazon mTurk).FindingsThe results confirmed that consumers are more likely to follow recommendations made by a human more than recommendations made by AI and the perceived creativity of the recommender explained the effect. Significant differences across product categories and shopping goals of the consumers were observed, calling for attention to the context of consumption.Originality/valueThis study extends the understanding of consumers' responses to recommendations in curation subscription services by highlighting the role of perceived creativity of humans versus AI.